THE EARLY MALADAPTIVE SCHEMAS’ AND ACHIEVEMENT MOTIVATION’S LINKS WITH THE SENSE OF THE SEVER ITY OF STRE SS AMONG MEN AND WOMEN - Zazulska, Klaudia; Wajs, Dżesika; Mącik, Dorota (Studia Psychologica: Theoria et praxis, 2017)
The aim of the presented study was to determine if and in what way early maladaptive schemas and achievement motivation influence the sense of stress in the groups of men and woman. 107 people, including 58 women and 49 men, in age between 21–59 were tested. Subject completed the Young Schema Questionnaire (YSQ-S3), the Achievement Motivation Inventory (LMI) and the Perception of Stress Questionnaire (KSP). A regression analysis showed differences between men and women. In case of women, schemas explain the external stress, while for men – internal stress. Achievement motivation influences all stress domains in a greater extend for women then for the men’s group. Motivation’s factors explain mostly emotional tension. For men’s group, models’ coefficients are weaker, the highest percentage of explained variance is observed for internal stress factor.